Economic and environmental effects of replacing bottom trawling with fishing with creels. (9th January 2021) - Hammarlund, Cecilia; Jonsson, Patrik; Valentinsson, Daniel; Waldo, Staffan
Abstract : Bottom trawling is associated with negative external effects such as seafloor pressure and high fuel use. Replacing bottom trawls with passive gear, such as creels, is therefore interesting for policymakers. We investigate the response of the Norway lobster fishery in Sweden to an expanded creel area. Using an economic model (FishRent), we analyse fleet structure, net present value and two environmental indicators under five management scenarios. Our results show that expanding the creel area increases the number of creel fishers, while some trawlers leave the fishery. In total, the net present value and the environmental performance of the fishery improve.